Pregnancy in Thalassemia and Sickle Cell Disease: The Experience of an Italian Thalassemia Center - Sorrentino, Francesco; Maffei, Laura; Caprari, Patrizia; Cassetta, Rita; Dell'Anna, Donatella; Materazzi, Stefano; Risoluti, Roberta (Frontiers in Molecular Biosciences, 2020)
The life expectancy of thalassemia patients has increased significantly in recent years being the most “elderly” patients approaching or are over 50 years old. Consequently, patients' perspectives have changed, leading them to longer-term planning with a consequent increase in their reproductive potential and desire to have children. Crucial points in the management of pregnancy in thalassemia are the iron chelation therapy before and during pregnancy, the antithrombotic prophylaxis, the management of transfusion therapy according to the modified transfusion requirement, a cardiologic monitoring for hemodynamic changes that expose an increased risk of heart failure. Pregnancy in women with sickle cell disease is still associated with increased rates of maternal and fetal mortality and adverse outcomes. Maternal morbidity may be due to acute sickling crises, thromboembolism, infection, and chronic end-organ dysfunction, while neonatal outcomes may be intrauterine growth retardation, preterm delivery, small infants for gestational age, stillbirth, and neonatal death. The management of pregnancy in thalassemia and sickle cell disease requires to be approached by a multidisciplinary team and followed from the pre-conception phase until the post-partum period with a close monitoring of the maternal and fetal conditions, in order to ensure optimal outcome. This approach requires the application of well-defined protocols that cover all the critical aspects of pregnancies in women affected by these pathologies. We describe our experience of spontaneous and non-spontaneous pregnancies in patients with thalassemia major and intermedia and sickle cell disease followed between 1992 and 2018 at the Thalassemia Unit of S. Eugenio Hospital of Rome.